Epidemiological Approach: Relationship Between Exclusive Breastfeeding with Undernutrition Among Children - Abdurrahman Al Hakim Sampurna Putra S, Ravenalla; Amadea Dyna Setyaji, Fidela (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Nutritional status is a health problem in the under-five age group in Indonesia.  An epidemiological approach was carried out to analyze the observations of children under five with poor nutritional status in the working area of ​​Puskesmas Kayon, Palangka Raya.  This research is a quantitative study using an analytical observational research design with the cross-sectional approach.  Data analysis in this study used the chi-square statistical test, to analyze the relationship between exclusive breastfeeding and the incidence of malnutrition.  Respondents in this study were mothers who had toddlers and lived in the working area of ​​the Puskesmas Kayon, Palangka Raya, with 80 people.  The results showed that there were 47 (58.8%) people who gave exclusive breastfeeding and 33 (41.2%) people did not give exclusive breastfeeding.  The chi-square test shows a p-value = 0.024, which means that there is a significant correlation between exclusive breastfeeding and the nutritional status of children under five.